A novel conflict resolution strategy in multi-agent systems: Concept and model - Basheer G.S.; Ahmad M.S.; Tang A.Y.C.; Ahmad A.; Mohd. Yusoff M.Z.; Mostafa S.A. (Springer Verlag, 2023)
In this paper, we present the concept and model of a conflict resolution strategy for a multi-agent system that covers all aspects of conflict processing, from collecting agents’ opinions, recognition of possible conflict status, and through a joint final decision. Our approach is to specify a novel structure for classifying conflict states in decision-making in which related factors, such as number of conflicting agents, agent’s confidence level and strength of conflict play essential roles in guiding and selecting the conflict resolution strategies. We provide an example scenario as a proof of concept to show the model’s applicability in multiple conflict situations. © Springer International Publishing Switzerland 2014.